Photoincorporation of puromycin and N-(ethyl-2-diazomalonyl)puromycin into Escherichia coli ribosomes. - Cooperman, B S (1975)
[3H]Puromycin and N-(ethyl-2-diazomalonyl)[3H]puromycin are incorporated into E. coli ribosomes on irradiation at 253.7 nm. Both compounds incorporate into both protein and nucleic acid. Two-dimensional gel electrophoresis of ribosomal protein shows that L23 is the major protein labeled by puromycin. Although incorporation is clearly a complex process, evidence is presented that L23 is labeled via an affinity labeling process, thus placing L23 at the aminoacyl-tRNA receptor (A) site. N-(ethyl-2-diazomalonyl)puromycin is a ribosomal ligand, as shown by its inhibition of two ribosomal assays, but it is not a good puromycin analog, and it is unclear whether its incorporation, which proceeds via both carbene-dependent and carbene-independent processes, results from affinity labeling.